The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/11038128.2020.1832145
|View full text |Cite
|
Sign up to set email alerts
|

Does the learning environment ‘make the grade’? A systematic review of accommodations for children on the autism spectrum in mainstream school

Abstract: Background: The 2030 Agenda for Sustainable Development adapted by the United Nations envisions inclusive and equitable quality education. While there is a growing body of research on interventions designed to help children on the autism spectrum adapt to the school environment, accommodations to children needs have been given less attention. Objective: To synthesize the literature on accommodations in the learning environment for children on the autism spectrum (ages 5-19 years) in mainstream school, with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 113 publications
0
9
0
1
Order By: Relevance
“…It is also viewed as an approach that should focus on improving the learning environment, routines, procedures, pedagogy, staff behaviors and attitudes, not manipulating students, which would follow the concept of "integration". However, the literature on specific inclusive educational actions is rather scare (13), and what inclusion should entail in practice for teachers and other school staff is often not specified and followed-up, or a matter of debate (14). Therefore, it is largely unknown, if and which concrete actions are currently implemented in mainstream schools by staff which could be subsumed as inclusive, although it has been hypothesized that inclusive practice remains poor for students with NDDs (15).…”
Section: Introductionmentioning
confidence: 99%
“…It is also viewed as an approach that should focus on improving the learning environment, routines, procedures, pedagogy, staff behaviors and attitudes, not manipulating students, which would follow the concept of "integration". However, the literature on specific inclusive educational actions is rather scare (13), and what inclusion should entail in practice for teachers and other school staff is often not specified and followed-up, or a matter of debate (14). Therefore, it is largely unknown, if and which concrete actions are currently implemented in mainstream schools by staff which could be subsumed as inclusive, although it has been hypothesized that inclusive practice remains poor for students with NDDs (15).…”
Section: Introductionmentioning
confidence: 99%
“…This review concluded that while evidence is emerging of the benefits of pedagogical and psychosocial accommodations in enabling outcomes for autistic students there is a need for innovative approaches and research methods to evaluate the role of environmental accommodations in improving outcomes. [ 61 ] Bearing testament to this conclusion was the finding that no study to date has examined the role of accommodations in the physical environment in improving outcomes in autistic children. Consistently research in the field of NDDs highlights that environmental factors, particularly organizational factors [ 62 ] and people in positions of authority in education systems, [ 60 ] can play in enabling inclusion and improving outcomes for autistic youth.…”
Section: The Icf For Modeling Environmental Determinants and Strengthsmentioning
confidence: 99%
“…I could not spontaneously name colleagues conducting research in autism and career guidance counseling or name any prominent articles or reviews on the topic. This, despite the fact that I have worked in closely connected fields and helped generate the International Society of Autism Research (INSAR) policy brief, 4 which is based on a systematic review, and a qualitative and quantitative study (Black et al, 2019, 2020; Scott et al, 2019), as well as other neighboring issues such as mentoring programs at universities and the significance of environmental adaptation to autistic students’ needs (Leifler et al, 2020; Thompson et al, 2019, 2020).…”
mentioning
confidence: 99%
“…Editorial significance of environmental adaptation to autistic students' needs (Leifler et al, 2020;Thompson et al, 2019Thompson et al, , 2020.…”
mentioning
confidence: 99%